2018
DOI: 10.1002/smll.201800136
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Surface Electronic Configuration of NiFe LDHs Nanosheets by Introducing Cation Vacancies (Fe or Ni) as Highly Efficient Electrocatalysts for Oxygen Evolution Reaction

Abstract: Intrinsically inferior electrocatalytic activity of NiFe layered double hydroxides (LDHs) nanosheets is considered as a limiting factor to inhibit the electrocatalytic properties for oxygen evolution reaction (OER). Proper defect engineering to tune the surface electronic configuration of electrocatalysts may significantly improve the intrinsic activity. In this work, the selective formation of cation vacancies in NiFe LDHs nanosheets is successfully realized. The as-synthesized NiFe LDHs-V and NiFe LDHs-V ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
218
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(225 citation statements)
references
References 26 publications
6
218
1
Order By: Relevance
“…Generally, tuning electronic structure of catalyst has proven to be an effective way to further enhance the OER performance through inducing oxygen and/or metal vacancies. [6,7] To decrease the free energy absorption of the OER intermediates (OH*, O*, and OOH*) and facilitate final product desorption is achievable for improving the overall OER performances. [8] Yanyong Wang et al reported that the NiFe LDHs-V Fe and NiFe LDHs-V Ni electrocatalysts with rich iron or nickel vacancies can show excellent OER activity, which is attributed to efficiently tuning surface electronic structure and increasing the adsorbing capacity of OER intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, tuning electronic structure of catalyst has proven to be an effective way to further enhance the OER performance through inducing oxygen and/or metal vacancies. [6,7] To decrease the free energy absorption of the OER intermediates (OH*, O*, and OOH*) and facilitate final product desorption is achievable for improving the overall OER performances. [8] Yanyong Wang et al reported that the NiFe LDHs-V Fe and NiFe LDHs-V Ni electrocatalysts with rich iron or nickel vacancies can show excellent OER activity, which is attributed to efficiently tuning surface electronic structure and increasing the adsorbing capacity of OER intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…The generated defects on the surface or in the lattice generally provide more active sites and significantly improve the electrochemical surface area (ECSA). For instance, Zn and Al templates were introduced to LDH nanosheet structures and then partially etched to form abundant pores on LDH nanosheets and to generate rich active sites . Liu and co‐workers replaced CO 3 2− anions with COOH − in the intercalation of CoFe LDH to achieve defective CoFe composites with enhanced OER activity .…”
Section: Regulation Effect In Multi‐metallic Oer Catalystsmentioning
confidence: 99%
“…[1] Rechargeable batteries are considered av ital approach fors ustainable energy storage and conversion to meet the increasing requirements of consumer electronics, electric vehicles,a nd the related energy industry. [2] Amongt he various battery configurations, rechargeable zinc-airb atteries demonstrate great potentiala sn ext-generation energy storaged evices because of their ultrahight heoreticale nergyd ensity of 1086Whkg À1 (including oxygen), [3][4][5][6] inherents afety originating from the use of aqueous electrolyte, [7] and additional advantages including low cost, [8] naturala bundance, [9] ande nvironmental benignity. [10] Therefore, developingh igh-performancer echargeable zinc-airbatteries has received extensive attention worldwide.…”
Section: Introductionmentioning
confidence: 99%